Volcanic passive continental margin beneath Maitri station in central DML, East Antarctica: constraints from crustal shear velocity through receiver function modelling - Gupta, Sandeep; Kanna, Nagaraju; Akilan, A (Polar Research, 2017)
Dronning Maud Land (DML) in East Antarctica is considered to be a key area for the reconstruction of the Gondwana supercontinent. We investigate the crustal shear wave velocity (Vs) model beneath the Maitri station, situated in the central DML of East Antarctica, through receiver function modelling. The analysis shows an average crustal thickness of 38.50 ± 0.5 km and a Vp/Vs ratio of 1.784 ± 0.002. The obtained Vs structure suggests that the topmost ca. 2.5 km of the crust contains ice and sediments with low Vs (1.5–2.0 km/s). This layer is underlain by a thick (ca. 12.5 km) layer of Vs = 2.25–2.6 km/s, suggestive of an extrusive igneous rock (rhyolite) at this depth range. Between 16 and 28 km depth, the Vs increases from 2.9 to 3.4 km/s. In the lower crust, a 7 km thick layer of Vs = 3.9 km/s is followed by 6 km thick underplated layer (Vs = 4.1 km/s) at the crust–mantle boundary. The uppermost mantle Vs is ca. 4.3 km/s. With the observation of underplated material in the lowermost crust, extrusive volcanic rocks in the upper crust, seaward dipping reflectors in the surrounding and a general paucity of seismicity, we believe the crust beneath the Maitri station represents a volcanic passive continental margin. We also believe that after its origin in the Precambrian and during its subsequent evolution it might have been affected by the post-Precambrian tectono-thermal event(s) responsible for the Gondwana supercontinent break-up.
Keywords: Dronning Maud Land; geofysikk; kontinentalmargin; seismologi; tektonikk; vulkaner

Transpression and tectonic exhumation in the Heimefrontfjella, western orogenic front of the East African/Antarctic Orogen, revealed by quartz textures of high strain domains - Bauer, Wilfried; Siemes, Heinrich; Spaeth, Gerhard; Jacobs, Joachim (Polar Research, 2016)
The metamorphic basement of the Heimefrontfjella in western Dronning Maud Land (Antarctica) forms the western margin of the major ca. 500 million year old East African/East Antarctic Orogen that resulted from the collision of East Antarctica and greater India with the African cratons. The boundary between the tectonothermally overprinted part of the orogen and its north-western foreland is marked by the subvertical Heimefront Shear Zone. North-west of the Heimefront Shear Zone, numerous low-angle dipping ductile thrust zones cut through the Mesoproterozoic basement. Petrographic studies, optical quartz c-axis analyses and x-ray texture goniometry of quartz-rich mylonites were used to reveal the conditions that prevailed during the deformation. Mineral assemblages in thrust mylonites show that they were formed under greenschist-facies conditions. Quartz microstructures are characteristic of the subgrain rotation regime and oblique quartz lattice preferred orientations are typical of simple shear-dominated deformation. In contrast, in the Heimefront Shear Zone, quartz textures indicate mainly flattening strain with a minor dextral rotational component. These quartz microstructures and lattice preferred orientations show signs of post-tectonic annealing following the tectonic exhumation. The spatial relation between the sub-vertical Heimefront Shear Zone and the low-angle thrusts can be explained as being the result of strain partitioning during transpressive deformation. The pure-shear component with a weak dextral strike-slip was accommodated by the Heimefront Shear Zone, whereas the north–north-west directed thrusts accommodate the simple shear component with a tectonic transport towards the foreland of the orogen. Keywords: Dronning Maud Land; quartz microfabrics; X-ray texture goniometry; shear zones; mylonites.
Keywords: Dronning Maud Land; geologi; mylonitter; petrografi; tektonikk

Tilt signals at Mount Melbourne, Antarctica: evidence of a shallow volcanic source - Gambino, Salvatore; Aloisi, Marco; Falzone, Giuseppe; Ferro, Angelo (Polar Research, 2016)
Mount Melbourne (74°21′ S, 164°43′ E) is a quiescent volcano located in northern Victoria Land, Antarctica. Tilt signals have been recorded on Mount Melbourne since early 1989 by a permanent shallow borehole tiltmeter network comprising five stations. An overall picture of tilt, air and permafrost temperatures over 15 years of continuous recording data is reported. We focused our observations on long-term tilt trends that at the end of 1997 showed coherent changes at the three highest altitude stations, suggesting the presence of a ground deformation source whose effects are restricted to the summit area of Mount Melbourne. We inverted these data using a finite spherical body source, thereby obtaining a shallow deflation volume source located under the summit area. The ground deformation observed corroborates the hypothesis that the volcanic edifice of Mount Melbourne is active and should be monitored multidisciplinarily.Keywords: Tilt monitoring; volcanic dynamics; physics volcanology; ground deformation; Victoria Land.
Keywords: Antarktis; geofysikk; tektonikk; vulkaner

The Main Shear Zone in Sør Rondane, East Antarctica: Implications for the late-Pan-African tectonic evolution of Dronning Maud Land - Ruppel, Antonia S; Läufer, Andreas; Jacobs, Joachim; Elburg, Marlina; Krohne, Nicole; Damaske, Detlef; Lisker, Frank (Tectonics, 2015)
Structural investigations in western Sør Rondane, eastern Dronning Maud Land (DML), provide new insights into the tectonic evolution of East Antarctica. One of the main structural features is the approximately 120 km long and several hundred meters wide WSW-ENE trending Main Shear Zone (MSZ). It is characterized by dextral high-strain ductile deformation under peak amphibolite-facies conditions. Crosscutting relationships with dated magmatic rocks bracket the activity of the MSZ between late Ediacaran to Cambrian times (circa 560 to 530 Ma). The MSZ separates Pan-African greenschist- to granulite-facies metamorphic rocks with “East African” affinities in the north from a Rayner-age early Neoproterozoic gabbro-tonalite-trondhjemite-granodiorite complex with “Indo-Antarctic” affinities in the south. It is interpreted to represent an important lithotectonic strike-slip boundary at a position close to the eastern margin of the East African-Antarctic Orogen (EAAO), which is assumed to be located farther south in the ice-covered region. Together with the possibly coeval left-lateral South Orvin Shear Zone in central DML, the MSZ may be related to NE directed lateral escape of the EAAO, whereas the Heimefront Shear Zone and South Kirwanveggen Shear Zone of western DML are part of the south directed branch of this bilateral system.
Keywords: Dronning Maud Land; geokronologi; geologi; geovitenskap; petrografi; tektonikk